(Re)Negotiating Caste Identities: Understanding the Response of the Balmiki Community during the Colonial Period. Issue 2 (December 2022) - Sabharwal, Monica
The Balmiki community has been the subject of various ethnographical studies. A lot has been written about what it has endured due to its contemptible social positioning. There still remain unexplored sites of struggles and experience, especially from the perspective of Balmikis as social actors. This study is an attempt to analyse and understand their responses to systemic oppression. The focus of the article is to understand the trajectory of the Balmiki community, which while navigating through myriad discourses, is trying to negotiate and renegotiate its identity. I intend to examine its situatedness in the tumultuous sociopolitical climate in Punjab and how it has articulated itself during the colonial period (late 19th century onwards) by placing reliance on colonial records and other literature pertaining to it. This article sheds light on the propensity of the community to reject the dominant values and reaffirm a distinct identity.